2014
DOI: 10.1128/microbiolspec.mgm2-0005-2013
|View full text |Cite
|
Sign up to set email alerts
|

Evasion of Innate and Adaptive Immunity byMycobacterium tuberculosis

Abstract: Through thousands of years of reciprocal coevolution, Mycobacterium tuberculosis has become one of humanity's most successful pathogens, acquiring the ability to establish latent or progressive infection and persist even in the presence of a fully functioning immune system. The ability of M. tuberculosis to avoid immune-mediated clearance is likely to reflect a highly evolved and coordinated program of immune evasion strategies that interfere with both innate and adaptive immunity. These include the manipulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 232 publications
(221 reference statements)
1
69
1
Order By: Relevance
“…In vivo , MAIT cell accumulation in the primary infected lung tissue starts less than 10 days post BCG infection, as detected by an MR1-tetramer for measuring the frequency of MAIT cells isolated from bronchoalveolar lavage fluid (BALF) and lung tissue (33). Taking into account the slow growing curve and immune-escaping mechanism mediated by M. tuberculosis as discussed (2, 76), the kinetics of MAIT cell responses is essentially faster than the response of conventional CD8 + T cells in the lung infection of M. tuberculosis (Figure 1A). It appears that both the in vitro and in vivo kinetics of MAIT cells upon mycobacterial infection can be considered to resemble that of conventional memory T cells (33, 88).…”
Section: Innate-like Postulate and Fast-responding Kineticsmentioning
confidence: 80%
See 1 more Smart Citation
“…In vivo , MAIT cell accumulation in the primary infected lung tissue starts less than 10 days post BCG infection, as detected by an MR1-tetramer for measuring the frequency of MAIT cells isolated from bronchoalveolar lavage fluid (BALF) and lung tissue (33). Taking into account the slow growing curve and immune-escaping mechanism mediated by M. tuberculosis as discussed (2, 76), the kinetics of MAIT cell responses is essentially faster than the response of conventional CD8 + T cells in the lung infection of M. tuberculosis (Figure 1A). It appears that both the in vitro and in vivo kinetics of MAIT cells upon mycobacterial infection can be considered to resemble that of conventional memory T cells (33, 88).…”
Section: Innate-like Postulate and Fast-responding Kineticsmentioning
confidence: 80%
“…Using a skin test, immune responses can be detected 5–6 weeks after M. tuberculosis infection in humans (74). In a drastic contrast to fast T cell responses to other intracellular bacteria, such as Listeria infection in mouse spleen (75), a much slower kinetics of T cell responses in M. tuberculosis infection may attribute to a slower growing curve of M. tuberculosis , bacterial inhibition of migratory activity, bacterial modulation of host antigen-presenting cells, and relatively immunoprivileged nature of the healthy alveolar tissues (2, 76). The antigen stimulation for conventional T cell activation occurs faster in vitro than in vivo because sufficient antigen presentation is usually warranted when setting up cell culture.…”
Section: Innate-like Postulate and Fast-responding Kineticsmentioning
confidence: 99%
“…M. tuberculosis employs several strategies to modulate effector CD4 T cell response (43). Several recent reports have indicated that PD-1–PD-L1/PD-L2 axis has a pivotal role in the regulation of T cell response to M. tuberculosis (29, 31, 33).…”
Section: Resultsmentioning
confidence: 99%
“…For each of these, M. tuberculosis has evolved the ability to inhibit or resist these defense mechanisms (Cambier et al, 2014; Goldberg et al, 2014). There is also increasing knowledge of “unconventional” or donor-unrestricted T cells (e.g., those with TCRs that interact with nonpolymorphic antigen-presenting molecules), including mycobacterial lipid antigen-specific T cells restricted by CD1a, CD1b, or CD1c (Van Rhijn and Moody, 2015), mucosal-associated invariant T cells (MAITs) (Gold et al, 2015), and γδ T cells.…”
Section: Mechanisms Of Immunity That Control M Tuberculosismentioning
confidence: 99%